Knowledge management practices in higher learning institutions in Sarawak / Abang Ahmad Ridzuan, Hong Kian Sam and Mohd Asri Adanan - Ridzuan, Abang Ahmad; Hong, Kian Sam (ACRULeT, Faculty of Education & UiTM Press, 2008)
This is a cross-sectional survey study designed to explore the views of lecturers in three higher education institutions in Kuching on knowledge management practices in their organizations. The three higher education institutions were Universiti Malaysia Sarawak (UNIMAS), MARA University of Technology Sarawak (UiTMCS) and Swinburne University of Technology Sarawak Campus. Questionnaires were used to collect data from the respondents regarding the importance lecturers attached to knowledge management and the levels of knowledge management implementation in the higher education institutions. The findings revealed that most of the lecturers at the higher education institutions felt that knowledge management was important and the lecturers placed the levels of knowledge management implementation at their institutions as moderate. There was a significant but weak positive relationship between importance attached to knowledge management and knowledge management implementation. Findings also revealed that there were significant differences in the importance attached to knowledge management based on the lecturers' gender and levels of education and a significant difference in the perceived levels of knowledge management implementation based on gender. However, there was no significant difference in the perceived levels of knowledge management implementation based on the lecturers' level of education.